2019
DOI: 10.1002/clen.201800376
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides from the EU First and Second Watch Lists in the Water Environment

Abstract: The contamination of water with pesticides used in agriculture and urban areas is a priority issue that is currently of global concern. In 2015, the European Union (EU) published the first Watch List (1st WL), which showed the necessity for Union‐wide monitoring of ten organic substances/groups of substances in the field of water policy. The list includes, among other items, eight pesticides: five neonicotinoids (acetamiprid, clothianidin, imidacloprid, thiacloprid, and thiamethoxam), and methiocarb, oxadiazon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 102 publications
0
44
0
1
Order By: Relevance
“…In the world, the reported concentrations of acetamiprid residues detected in water ecosystems are respectively 6.31 mg/L in Brazil, 34.4 ng/L in China and 40 ng/L in the United States (Yi et al, 2019;Hladik and Kolpin, 2016;Carbo et al, 2008). Those concentrations are lower than the LC50-96 h determined in Nile tilapia Oreochromis niloticus (Guedegba et al, 2019) but may constitute a risk for a good ecological status of water bodies because of its high solubility in water (Pietrzak et al, 2019).…”
Section: Introductionmentioning
confidence: 68%
“…In the world, the reported concentrations of acetamiprid residues detected in water ecosystems are respectively 6.31 mg/L in Brazil, 34.4 ng/L in China and 40 ng/L in the United States (Yi et al, 2019;Hladik and Kolpin, 2016;Carbo et al, 2008). Those concentrations are lower than the LC50-96 h determined in Nile tilapia Oreochromis niloticus (Guedegba et al, 2019) but may constitute a risk for a good ecological status of water bodies because of its high solubility in water (Pietrzak et al, 2019).…”
Section: Introductionmentioning
confidence: 68%
“…Neonicotinoid levels in surface water were reviewed earlier by Morrissey and coworkers [39]. A number of monitoring studies reported the occurrence and levels of neonicotinoids in surface water ( Figure 5) [22,39,40]. Elevated detection frequencies (98.7%-100%) and maximum concentrations were reported from high maize and soybean producing regions, and the transport of the residues was found to be driven also by precipitation.…”
Section: The Presence Of Neonicotinoids In Surface Watersmentioning
confidence: 99%
“…Elevated detection frequencies (98.7%-100%) and maximum concentrations were reported from high maize and soybean producing regions, and the transport of the residues was found to be driven also by precipitation. [22,39,40]. The indicated quality reference values: European Food Safety Authority (EFSA) no observable effect concentration (NOEC) [41], Rijksinstituut voor Volksgezondheid en Milieu (RIVM) Nederland maximum permissible concentration and long term exposure [42,43], US-EPA aquatic life benchmark [44], Canadian Council of Ministers of the Environment (CCME), water quality guideline [45], Australia and New Zealand proposed aquatic ecosystem protection guideline values depending on species protection goals (80%-99%) [46] and a default guideline value proposed by third parties is under peer review process [47].…”
Section: The Presence Of Neonicotinoids In Surface Watersmentioning
confidence: 99%
“…Each has a pair of broad absorption features below 280 nm. Tryptophan is an amino acid whose UV fluorescence is similar to that of organic matter such as sewage and farm slurry 31 . This shows a broad peak around 280 nm (absorption here is also associated with fluorescence at 340 nm) and a sharper peak at 220 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Metaldehyde, a pesticide for slugs and snails, absorbs rather weakly across the UV range studied and we found that it was not possible to reliably detect this compound with UV LEDs of wavelength 250 nm and above. Uric acid is present in untreated sewage but is not normally found in unpolluted waters 32 . It shows broad peaks at around 235 and 290 nm, and a peak or edge at 200 nm.…”
Section: Resultsmentioning
confidence: 99%